+0  
 
0
60
1
avatar

Solve 2/3*(a - 14) = -3(a - 3).

 Jul 17, 2020
 #1
avatar+21953 
0

Solve:     (2/3)·(a - 4)  =  -3(a - 3)

 

Multiply both sides by 3:            3·[ (2/3)·(a - 4) ]  =  3·[ -3·(a - 3) ]

                                                               2·(a - 4)  =  -9·(a - 3)

Distribute:                                                   2a - 8  =  -9a + 27

Add  9a  to both sides;                              11a - 8  =  27

Add  8 to both sides:                                      11a  =  35

Divide both sides by 11:                                   a  =  35/11

 Jul 17, 2020

37 Online Users

avatar
avatar
avatar